Meditation and auditory attention: An ERP study of meditators and non-meditators - Biedermann, Britta; de Lissa, P.; Mahajan, Y.; Polito, V.; Badcock, N.; Connors, M.; Quinto, L.; Larsen, L.; McArthur, G. (Elsevier BV, 2016)
The findings of a study by Cahn and Polich (2009) suggests that there is an effect of a meditative state on three event-related potential (ERP) brain markers of “low-level” auditory attention (i.e., acoustic representations in sensory memory) in expert meditators: the N1, the P2, and the P3a. The current study built on these findings by examining trait and state effects of meditation on the passive auditory mismatch negativity (MMN), N1, and P2 ERPs. We found that the MMN was significantly larger in meditators than non-meditators regardless of whether they were meditating or not (a trait effect), and that N1 amplitude was significantly attenuated during meditation in non-meditators but not expert meditators (an interaction between trait and state). These outcomes suggest that low-level attention is superior in long-term meditators in general. In contrast, low-level attention is reduced in non-meditators when they are asked to meditate for the first time, possibly due to auditory fatigue or cognitive overload.